Aggregation-induced emission generation via simultaneous N-alkylation and rhenium(I) tricarbonyl complexation for 2-(2-thienyl)imidazo[4, 5-f][1, 10]-phenanthroline. (March 2020) - Liu, Hua-Qi; Peng, Yu-Xin; Zhang, Yi; Yang, Xi-Qiang; Feng, Fan-Da; Luo, Xu-Biao; Yan, Liu-Shui; Hu, Bin; Huang, Wei
Abstract: In this paper, imidazole N -alkylation (allyl and n -butyl) and the following rhenium(I) complexation strategy have been used for 2-(2-thienyl)imidazo[4, 5- f ][1, 10]-phenanthroline (TIP) to generate two aggregation-induced emission (AIE) active rhenium(I) tricarbonyl complexes Re2 and Re3 . The destroy of planarity and conjugation of TIP by introducing alkyl chains and the increase of steric hindrance via implanting octahedral Re(I) coordination sphere lead to the restrictions of intramolecular rotation and formation of intermolecular π-π stacking, which could be the main reasons for the AIE activation. X-ray single-crystal structures of Re1 and Re2 verify the increase of dihedral angle in the TIP skeleton from 10.8(5) o to 22.7(1) o as well as the different crystal packing fashions (AAAA vs ABAB) after introducing the spatial crowding allyl group. Further studies reveal that the above-mentioned simultaneous modifications are vital for the AIE generation because control experiments show that either single imidazole N -alkylation (L2 and L3 ) or single rhenium(I) tricarbonyl complexation (Re1 ) gives rise to the typical aggregation-caused fluorescence quenching. To the best of our knowledge, this is the first report on Re(I)-TIP complexes and corresponding dual functionality for the AIE activation. Graphical abstract: Image 1 Highlights: N -alkylation and Re(I) complexation are performed to prepare TIP derivatives. Dual functionality for the planar TIP molecule to generate AIE is achieved. AIE mechanism is described based on crystal structures and spectral observations.